Medium- and long-term consequences of pollution on labor supply: Evidence from Indonesia - Younoh Kim; James Manley; Vlad Radoias (IZA Journal of Labor Economics, 2017)
We use a natural experiment in Indonesia to study the medium- and long-term effects of air pollution on labor supply. We find that exposure to air pollution reduces hours worked and while the medium-term effects are larger in magnitude, some effects do persist in the long term. More interestingly, we are able to provide some insight regarding the underlying channels that contribute to the reduced labor supply. Own health seems to be the only responsible channel in the long term, while in the medium term, a different channel based on dependent caregiving is the most important.
Keywords: J22; Q53; 330; Air pollution; Working hours; Indonesia